Chemically modified oxide surfaces : proceedings of the Chemically Modified Surfaces Symposium, Midland, Michigan, June 28-30, 1989 - Chemically Modified Surfaces Symposium (2nd : 1989 : Midland, Mich.); Leyden, Donald E., 1938-; Collins, Ward T. (New York : Gordon and Breach Science Pub., 1990)
09